Penerapan Standar Proses Keperawatan di Puskesmas Rawat Inap Cilacap - Susanto, Rachmat (Jurnal Keperawatan Soedirman, 2010)
The objective of health development is to improve the ability of healthy life for everyone. One of the health service conducted at community health centers. Problems found in the standard application of nursing process is still not optimal. If the application is not optimal standards of nursing process, the quality of health services is also not good. This observational descriptive study to determine the application of nursing process standard inpatient community health centers in the regency of Cilacap. As many as seven community health centers conducted observations. Observations have been conducted found that the application data from the nursing process assessment, diagnosis, planning, implementation and evaluation, not well implemented. The researcher give suggestions for improving the quality of nursing services with the application of nursing process is either through the addition of facilities and equipment, awards and evaluations.